Individual and Relational Outcomes of Inter-religious Marriage: A Scoping Review - Cyriac, Jineesh (Journal of religion and health, 2026)
Inter-religious marriages, where partners come from different religious affiliations, pose unique challenges and opportunities. This scoping review aims to examine the literature on individual and relational outcomes of inter-religious couples and their families, synthesising existing evidence on their social, psychological, and cultural aspects. While numerous studies exist on this topic, their findings have not yet been systematically synthesised. The question for this scoping review was how existing studies explore the individual and relational outcomes of interfaith marriages. A comparative search, following Arksey and O'Malley's five-step framework and PRISMA-ScR guidelines, was conducted across Scopus, ScienceDirect, APA PsycNet, JSTOR, PubMed, Google Scholar, and ProQuest databases from 2004 to 2024. After screening 1,276 references based on inclusion criteria, 19 peer-reviewed articles were selected for the scoping review. Four key themes emerged: (1) Marital adjustment and tensions, (2) Psychological impacts, (3) Marital instability and dissolution, and (4) Strengths and opportunities. This scoping review emphasises the intricate challenges encountered by inter-religious couples, encompassing familial opposition, identity dilemmas, cultural and religious disputes, marital instability, and psychological distress. The review highlights the need for increased societal and institutional support and calls for further research into adaptive coping strategies across diverse cultural contexts.